2013
DOI: 10.1210/jc.2012-3324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Risk Factors for Type 2 Diabetes at Early or Late Post Partum After Gestational Diabetes Mellitus

Abstract: Obesity was a risk factor for both early and late T2DM converters. However, early converters had more pronounced defects in β-cell function, which might be explained, in part, by differences in genetic predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 39 publications
5
86
3
1
Order By: Relevance
“…The other representative study indicated a positive association of prepregnancy BMI with postpartum T2D risk (20). The present study with large sample size, long follow-up, and large incident cases of T2D and prediabetes during follow-up demonstrated that prepregnancy overweight and obesity had a hazardous effect on the risks of T2D and prediabetes among GDM women after delivery.…”
Section: Obesitysupporting
confidence: 43%
See 1 more Smart Citation
“…The other representative study indicated a positive association of prepregnancy BMI with postpartum T2D risk (20). The present study with large sample size, long follow-up, and large incident cases of T2D and prediabetes during follow-up demonstrated that prepregnancy overweight and obesity had a hazardous effect on the risks of T2D and prediabetes among GDM women after delivery.…”
Section: Obesitysupporting
confidence: 43%
“…Until now, only two studies have assessed the association of prepregnancy BMI with the risk of postpartum T2D among prior GDM women (19,20). One study did not find any associations between prepregnancy BMI and T2D risk, The significance of the trend over different categories was tested in models with the median of each category as a continuous variable.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation has shown that women with Japanese GDM have beta cell dysfunction irrespective of presence or absence of overweight [25]. Regarding the genetic background, several studies revealed risk variants related to insulin secretion in Korean and Chinese population [36][37][38][39][40][41]. Of the three genetic variants found in this study, two are related to the regulation of insulin secretion (i.e.…”
Section: Discussionsupporting
confidence: 48%
“…Since women with GDM are at a high risk of future T2DM, genetic information on GDM would be useful for the T2DM risk classification [38,41]. Further research using a larger cohort is warranted for better understanding the genetics of GDM in Japanese women.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the pathogenesis of GDM is not clear, but GDM and T2D share several common risk factors and have a similar pathophysiology that includes glucose intolerance, insulin resistance, and impaired insulin secretion (Ryan et al, 2013). Additionally, women with a history of GDM are at an increased risk of GDM during subsequent pregnancies (Kwak et al, 2013). Several studies have shown that genetic factors play an important role in GDM occurrence (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%